Modified Grid-Connected CSI for Hybrid PV/Wind Power Generation System - D. Amorndechaphon; S. Premrudeepreechacharn; K. Higuchi; X. Roboam (International Journal of Photoenergy)
The principle of a power conditioning unit for hybrid PV/wind power generation system is proposed. The proposed power conditioner is based on the current source inverter (CSI) topology. All energy sources are connected in parallel with a DC-bus through the modified wave-shaping circuits. To achieve the unity power factor at the utility grid, the DC-link current can be controlled via the wave-shaping circuits with the sinusoidal PWM scheme. In this work, the carrier-based PWM scheme is also proposed to minimize the utility current THD. The power rating of the proposed system can be increased by connecting more PV/wind modules through their wave-shaping circuits in parallel with the other modules. The details of the operating principles, the system configurations, and the design considerations are described. The effectiveness of the proposed CSI is demonstrated by simulation results.